La automatización laboral: una perspectiva fenomenológica e histórica - García Uribe, Jhon Camilo; Rico Areiza, Luisa Fernanda (Jangwa Pana, 2022)
Throughout the history of humanity, technique, science and technology have played a fundamental role, not only because of the benefits that their development has brought with it —either because individuals can see them for themselves, or because the externality which they make up has forced them to be seen that way— but also because of their effects, direct and indirect, or simply because such advances cannot even be accessed, because they are not for everyone. The automation of the operational workforce is one of these scientific-technological advances that have taken the essence of technology to a new level, technifying life, social interactions and the functions performed by humans. The end is to dispense with humanity, where everything and everyone is replaceable, where the care of the other is not conceived. Consumption, increased productivity and the attainment of wealth for a few are promoted. Its consequences are the increase in poverty, the widening of the wealth gap and technological illiteracy, among other detrimental effects. This writing analyzes the automation of employment, the external factors that have influenced technological progress and the aspect that few recognize about automation: the displacement of the human being at the hands of technology, its already evident consequences, and the possible future.